The Effectiveness of the Value Clarification Technique in Learning History for High School Students in Bekasi - Budi Purnomo; Sigit Widiyarto (AL-ISHLAH: Jurnal Pendidikan, 2023)
Learning history is beyond the material delivery. It needs to convey the value contain in the past event that can be internalized in the characters of high school students. That value can be developed into a complete and undivided understanding. This research has an experimental scheme. Experimental study were carried out to test the Value Clarification Technique (hereafter, VCT) method in History lessons on the history of youth oaths, figures and the meaning behind them. The aim of the study was to find out the history learning process using the VCT method for class XI students at and find out whether the VCT method could improve learning outcomes in history material on the history of youth oaths, figures and the meaning behind it for students of class XI .Data collection techniques were conducted by interviews, documentation, and tests where the instrument tests were carried out before and after treatment in the same class. This study explained that the learning process was able to explore and clarify alternative values. VCT was effective in increasing and facilitating the inculcation of values in the material. Teachers are advised to diversify VCT learning aids so that students can explore more of all another media.